2015
DOI: 10.22452/mjs.vol34no1.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tempeh as a Potential Alternative Protein Source in the Diets for Juvenile Tiger Grouper, Epinephelus Fuscoguttatus

Abstract: A 56-day feeding trial was conducted to evaluate the potential of replacing fishmeal (FM) with tempeh (TMP) in the diets for juvenile tiger grouper (TG), Epinephelus fuscoguttatus. Five isoproteic (50%) and isolipidic (16%) diets containing FM replaced by TMP at 0, 30, 40, 50% (namely TMP0, TMP30, TMP40, TMP50, respectively), and by 30% soybean meal supplemented with phytase (SBM30) were fed to triplicate group of fish (10.09±0.15g). Weight gain (WG) and feed intake (FI) of TMP0 group were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…This study reported that the FCR of the hybrid grouper fed with SPC‐based feed ranged from 0.83 to 1.31. The FCR value was better than other grouper species (Chor et al., ; García‐Ortega et al., ; Shapawi, Ebi & Yong, ; Shapawi, Ebi, Yong, Chong et al., ). However, increasing the SPC from 30% to 60% led to higher FCR and lower PER and NPU value compared to control and other lower replacement levels.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This study reported that the FCR of the hybrid grouper fed with SPC‐based feed ranged from 0.83 to 1.31. The FCR value was better than other grouper species (Chor et al., ; García‐Ortega et al., ; Shapawi, Ebi & Yong, ; Shapawi, Ebi, Yong, Chong et al., ). However, increasing the SPC from 30% to 60% led to higher FCR and lower PER and NPU value compared to control and other lower replacement levels.…”
Section: Discussionmentioning
confidence: 81%
“…In a study that replaced fish meal with FSM and DSM in the feed for brown‐marbled grouper, Chor et al. () discovered that the fish fed with 30%, 40% and 50% of FSM attained lower growth compared to control and feed with 30% of DSM in a 56‐day feeding trial. However, among the FSM‐based feed, brown‐marbled grouper fed with 40% of FSM showed significantly better ( p < .05) growth (Chor et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations